Double orifice mitral valve – A case report - Musić, Ljilja B; Knežević, Božidarka; Jovović, Ljiljana; Bulatović, Nebojša (Vojnosanitetski pregled, 2017)
Introduction. Double orifice mitrol valve (DOMV) is a very rare congenital heart defect. Case report. We reported 20-year-old male referred to our center due to evaluation of his cardiologic status. He was operated on shortly after birth for a tracheoesophageal fistula. Accidentally, echocardiography examination at the age of 4 years revealed double orifice mitral valve (DOMV) without the presence of mitral regurgitation, as well as mitral stenosis, with normal dimensions of all cardiac chambers. The patient was asymptomatic, even more he was a kick boxer. His physical finding was normal. Electrocardiography showed regular sinus rhythm, incomplete right bundle branch block. Transthoracic echocardiography (TTE) examination revealed the normal size of the left atrial, mitral leaflets were slightly more redundant. The left and right heart chambers, aorta, tricuspid valve and pulmonary artery valve were normal. During TTE examination on a short axis view two asymmetric mitral orifices were seen as a double mitral orifice through which we registered normal flow, without regurgitation and mitral stenosis. Transesophageal echocardiography (TEE) examination from the transgastric view at the level of mitral valve, showed 2 single asymmetric mitral orifices separated by fibrous tissue, mitral leaflet with a separate insertion of hordes for each orifice. Conclusion. The presented patient with DOMV is the only one recognized in our country. The case is interesting because during 16-year a follow-up period there were no functional changes despite the fact that he performed very demanded sport activities. This is very important because there is no information in the literature about that.